Construction of Hcp immunohistochemical library and antibody expression based on single memory B cell sequencing technology - ZHOU Jinrui; WANG Wenhao; GU Yaru (陆军军医大学学报)
Objective‍　‍To prepare humanized monoclonal antibodies (Mabs) targeting Acinetobacter baumannii (Ab) based on single memory B cell sequencing technology, construct the immune repertoire of the core protein of Ab, hemolysin-coregulated protein (Hcp), and express its Mabs with binding activity. Methods‍　‍E. coli BL21 harboring the recombinant plasmid pGEX-6p-1-Hcp was constructed. Hcp protein was obtained using protein expression and affinity chromatography. Female SPF BALB/c mice (6~8 weeks old, weighing 18~20 g) were immunized intramuscularly with antigen Hcp to generate specific memory B cells. Single antigen-specific memory B cells were sorted using flow cytometry. The immune repertoire of Hcp was constructed using single-cell sequencing technology, and bioinformatics analysis was performed on the sequencing results. Mabs were obtained using antibody humanization techniques. The in vitro binding activity of the antibodies was detected by ELISA. Results‍　‍The target protein Hcp with a purity >95% was obtained after expression and purification. The immune repertoire of Hcp was successfully constructed, and the results of BCR clonotype identification and analysis, CDR3 region characteristic analysis, and V-J gene pairing characteristic analysis were achieved. Antibody humanization got 7 Mabs, that is, IgG1-1, IgG1-2, IgG2-1, IgG2-2, IgG3-1, IgG4-1 and IgG4-2. ELISA results showed IgG1-1, IgG3-1, IgG4-1, and IgG4-2 had an antibody binding titer of 1∶1 280, IgG2-2 of 1∶10 240, IgG2-1 of 1∶5 120, and IgG1-2 of 1∶160. Conclusion‍　‍Single-cell sequencing technology enables rapid, accurate, and efficient construction of an Hcp protein immune repertoire containing extensive antibody information. Utilizing this immune repertoire allows for the expression of Mabs with binding activity.